1998
DOI: 10.1002/(sici)1521-3765(19980807)4:8<1458::aid-chem1458>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Positive Effect of Cadmium Acetate on the Action of Supported Palladium Catalysts

Abstract: The complex chemistry of Pd(OAc) 2 and Cd(OAc) 2 in the solid state and in acetic acid solution has been studied. Triclinic crystals, space group P1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In Figure S2, the N 1s and the Cd 3d core levels of 5j are depicted. The measured binding energy of the Cd 3d 5/2 core level (406.0 eV) is indeed close to the binding energy measured for related Cd 2+ complexes (405.7 eV) . An additional contribution of nitrogen in NO 2 groups would also appear at 406 eV binding energy (see Figure ).…”
Section: Resultssupporting
confidence: 81%
“…In Figure S2, the N 1s and the Cd 3d core levels of 5j are depicted. The measured binding energy of the Cd 3d 5/2 core level (406.0 eV) is indeed close to the binding energy measured for related Cd 2+ complexes (405.7 eV) . An additional contribution of nitrogen in NO 2 groups would also appear at 406 eV binding energy (see Figure ).…”
Section: Resultssupporting
confidence: 81%
“…Because the dehydrogenation is endothermic K p increases with temperature. Bond et al have shown that the value of x does not significantly affect the rate. A similar behavior was found in this work and therefore a constant value for each paraffinic GOI was set for x .…”
Section: Rate Expressions For Reactions On Metal Sitesmentioning
confidence: 99%
“…However, synthesis and processing of such parent compounds is rather laborious. Pd-based heterobimetallic carboxylate complexes could be viable alternative precatalysts; however, until recently, there were only two well-defined examples for this type of compound -Pd 2 Cd 2 (l-OO CMe) 8 AE(HOOCMe) 2 [3] and PdTl(l-OOCMe) 4 (OO CMe) [4].…”
Section: Introductionmentioning
confidence: 99%